Boston Consulting Group (BCG'S) Analysis On Powder Coffee 1001 Bengkulu City - Dian Safitri; Sulisti Afriani; Eska Prima Monique Damarsiwi (Journal of Indonesian Management, 2021)
In implementing the marketing strategy, it is always related to marketing recommendations consisting of four variables, namely: product, price, place, promotion. BCG analysis is based on the basic premise that a company should have a balanced portfolio of business, which produces more than the amount it uses. Its role is determined by two factors, namely: (1) Market Growth Rate (2) Relative Market Share. The BCG analysis has 4 cells representing 4 combinations showing the lowest growth rate and market share, namely: stars, cash cows, dogs, and question marks. The data collection methods used in this writing were the observation method, the interview method (unstructured), and the documentation method. BCG analysis was carried out based on data on the sales volume of Usaha Kopi Bubuk 1001 of Bengkulu City in 2018 and 2019 which were compared with the sales volume data of Usaha Kopi Bubuk Aroma in 2019, to obtain a relatively high level. From the results of research with BCG analysis, it can be seen that the market growth rate of Usaha Kopi Bubuk 1001 of Bengkulu City in 2019 is 14% and the relative market share is 1.6x, then Usaha Kopi Bubuk 1001 of Bengkulu City is in the Star position, which indicates that growth high market and relatively high market share, and it is related to the Product Life Cycle, the product position of Usaha Kopi Bubuk 1001 of Bengkulu City is in the Growth stage, so the strategy used by Usaha Kopi Bubuk 1001 of Bengkulu City is the Hold strategy.